2013
DOI: 10.4187/respcare.02570
|View full text |Cite
|
Sign up to set email alerts
|

Meditative Movement for Respiratory Function: A Systematic Review

Abstract: BACKGROUND:Meditative movement, such as tai chi, yoga, and qi gong, may benefit people with cystic fibrosis (CF), as a form of gentle exercise incorporating meditation, breathing, and relaxation. Respiratory function is the most common issue in CF. In this systematic review we synthesized the evidence on the effect of meditative movement on respiratory function in patients with CF. METHODS: We searched Chinese and English language databases with terms relating to tai chi/yoga/qi gong, and respiratory function/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 62 publications
(105 reference statements)
0
14
0
Order By: Relevance
“…Effectively, previous systematic studies and meta-analyses investigated the efficacy of cognitive behavioral or psychotherapeutically based interventions and progressive muscle relaxation, though not distinguishing them [ 16 ]. Others examined the effects of education, exercise, and/or psychosocial support [ 65 ] in COPD patients, the effects of psychologically based treatments only on anxiety and panic in people with COPD [ 66 ], or the improvements in respiratory functions in people with Cystic Fibrosis (CF) generated by meditative movements [ 67 ]. Finally, other authors investigated the effectiveness of nonpharmacological and noninvasive interventions to relieve breathlessness in participants with advanced stages of cancer, Chronic Obstructive Pulmonary Disease (COPD), interstitial lung disease, chronic heart failure, or motor neuron disease [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Effectively, previous systematic studies and meta-analyses investigated the efficacy of cognitive behavioral or psychotherapeutically based interventions and progressive muscle relaxation, though not distinguishing them [ 16 ]. Others examined the effects of education, exercise, and/or psychosocial support [ 65 ] in COPD patients, the effects of psychologically based treatments only on anxiety and panic in people with COPD [ 66 ], or the improvements in respiratory functions in people with Cystic Fibrosis (CF) generated by meditative movements [ 67 ]. Finally, other authors investigated the effectiveness of nonpharmacological and noninvasive interventions to relieve breathlessness in participants with advanced stages of cancer, Chronic Obstructive Pulmonary Disease (COPD), interstitial lung disease, chronic heart failure, or motor neuron disease [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“… 4 Yoga has the potential to be beneficial for patients with CF by impacting many aspects of their disease; however, yoga has not previously been investigated in patients with CF. 13 There are several potential mechanisms by which yoga may benefit patients with CF, including improved airway clearance secondary to deep-breathing exercises and strengthening of respiratory muscles. The potential psychosomatic effects of yoga include stress reduction and an improved sense of wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…After systematic review [75, 76] we found only one prior study performed by Ruddy et al to evaluate yoga as a complementary therapeutic practice in children with cystic fibrosis [76]. The study presented here is the largest to date and the first with a primary aim is to evaluate therapeutic benefit; however, this is a pilot study and the results should be considered suggestive but not conclusive.…”
Section: Discussionmentioning
confidence: 90%